1989
DOI: 10.1210/jcem-68-6-1201
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline: Long-Acting Oral Treatment of Hyperprolactinemic Disorders

Abstract: Cabergoline, a new orally active dopaminergic drug with an extremely long-lasting PRL-lowering effect, was given to 48 hyperprolactinemic women for 3-18 months (median, 8 months) at doses varying between 0.2-3 mg/week administered one to three times weekly. Serum PRL levels declined to normal in 41 women, 30 of whom received 0.2-1 mg cabergoline once weekly, 8 received 0.2-0.5 mg twice weekly, and 3 received 0.4-0.6 mg 3 times weekly. Five women had slightly supranormal serum PRL levels while receiving 0.3-0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…Those authors found that a single oral dose of CG induced a marked fall in serum PRL level that persisted for 72 h in rats [10], and for 7 days in humans [15].…”
Section: Light Microscopymentioning
confidence: 97%
See 2 more Smart Citations
“…Those authors found that a single oral dose of CG induced a marked fall in serum PRL level that persisted for 72 h in rats [10], and for 7 days in humans [15].…”
Section: Light Microscopymentioning
confidence: 97%
“…Thus, CG induced a prolonged lowering of PRL and had a good antitumor effect on rat pituitary tumors induced by estrogen. Correspondence to: Dr. Kuniki EGUCHI, Department of Neurosurgery, Hiroshima University School of Medicine, 1-2-3 Kasumi, Minami-ku, Hiroshima 734, Japan also exhibits a potent PRL-lowering effect and an antitumor effect in animals and humans [10][11][12][13][14][15][16][17]. Its mechanism of action in reducing tumor size has never been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These reactions are likely due to the rapid absorption of the drug which is administered two or three times a day, thus causing high blood levels. In order to improve the tolerance, several drugs with differ ent molecular structure or half-life have been tested: some are ergot derivatives with half-lives similar to (lisuride, pergolide, mesulergine) [6,7] or longer than BRC (caber goline) [8], others represent new formulations of BRC with different pharmacokinetics providing a long-lasting effect in monthly i.m. injection (BRC-LAR) [9][10][11][12][13] or in single daily oral administration (BRC-SRO) [13][14][15], Fi nally, there is a non-ergot derivative which selectively binds dopamine D?…”
Section: Introductionmentioning
confidence: 99%
“…In fact, BRC and lisuride are ergot-derived drugs while CV 205-502 is a nonergotderived drug [6,7], The poor tolerance to the conven tional therapy with BRC has caused the introduction in clinical practice of other drugs, i.e. lisuride, pergolide, lergotrile, metergoline, cabergoline [8,9] and new formula tions of BRC characterized by slow release, such as the injectable and repeatable form (Parlodel LAR) and the slow oral release form (Parlodel SRO) [10][11][12], All these drugs are ergot-derived dopamine agonists. They are effective in the medical treatment of hyperprolactinemic states and represent a good alternative in patients resis tant or intolerant to BRC.…”
Section: Discussionmentioning
confidence: 99%